Three-Dimensional Minute-Scale Displacement of Fels Slide Measured With Multistation Ku-Band Ground-Based Radar - Farnoush Hosseini; Bernhard Rabus; Franz J. Meyer; Davide Donati; Doug Stead; John J. Clague (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Fels slide is an active deep-seated gravitational slope deformation (DGSD) in the northern slope of the Fels Glacier Valley, Alaska. Proximity to critical infrastructure of the Richardson Highway and the Trans-Alaska Pipeline makes this landslide a prime target for detailed monitoring. This study aims to show the potential of measuring slow, short-term three-dimensional slope deformations with ground-based interferometric real aperture radars. We present a methodological framework for processing ground-based radar data that corrects complex atmospheric effects to uncover the relatively small subdaily deformation rates of the Fels slide and similar DGSDs. We acquired high temporal resolution ground-based interferometric real aperture radar images from two $Ku$ -band GAMMA remote sensing portable radar interferometers (GPRIs) installed on a stable slope facing the slide, operating at five-minute sampling interval over multiday periods in July 2017 and 2018. Line of sight (LOS) deformations derived from the differential interferometric phase of the acquired images for both stations were affected by atmospheric water vapor in complicated ways. We developed and applied a novel comprehensive multistep correction scheme to remove atmospheric bias, including separate corrections of static, dynamic (turbulent), and fog bank-induced contributions. The proposed method achieves significant improvements in the accuracy of the retrieved LOS displacement for the actively deforming regions of the landslide. After geocoding, the corrected LOS deformations from the two stations were combined with an additional motion direction constraint from repeat light detection and ranging measurements over a longer two-year period to invert three-dimensional motion vectors. We used regularization to robustly mitigate the suboptimal observation geometry caused by logistical constraints on station placement. Our results reveal hitherto unknown spatial details and subdaily temporal variations of the three-dimensional deformation field of Fels slide and provide new insights into its failure mechanism.